Art of the pie : a practical guide to homemade crusts, fillings, and life - McDermott, Kate, 1953- (Countryman Press, 2016)
"Pie-making should be simple and fun. Kate McDermott has taught this and made pies with thousands of people across the country at her Pie Camps. Her confidence comes through in every recipe, and will inspire readers to don an apron, grab a rolling pin, and get cooking. (The stunning photographs in this book won't hurt either.) Over the years, McDermott developed more than a dozen crusts, half of which are gluten-free, and in this book she gives detailed instructions for making, rolling, and baking crusts. A pie needs filling, too, and she does not neglect a single detail when describing her ingredients, methods, and tricks for making the filling and finishing off the pie. Art of the Pie is more than a cookbook. Kate's rules extend well beyond pie baking: keep everything chilled, respect the boundaries, and remember to vent. This is a book to keep close at hand,"--Amazon.com.